10 secrets to sporting success : professionals reveal their mind training secrets : follow this step-by-step guide to reach your true potantial and to coach others to reach theirs /: professionals reveal their mind training secrets : follow this step-by-step guide to reach your true potantial and to coach others to reach theirs. (2015) - Page, Katie; Clarke, Helen
No abstract available